2010
DOI: 10.1007/s11192-010-0221-9
|View full text |Cite
|
Sign up to set email alerts
|

News in brief and features in New Scientist magazine and the biomedical research papers that they cite, August 2008 to July 2009

Abstract: New Scientist is a British weekly magazine that is half-way between a newspaper and a scientific journal. It has many news items, and also longer feature articles, both of which cite biomedical research papers, and thus serve to make them better known to the public and to the scientific community, mainly in the UK but about half overseas. An analysis of these research papers shows (in relation to their presence in the biomedical research literature) a strong bias towards the UK, and also one to the USA, Scandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…A third were about breast cancer followed by lung (10%), prostate (8%), and skin (6%) cancer. Journalists working for the New Scientist read and use a wide range of academic journals, especially general and medical titles including Proceedings of the National Academy of Sciences of the USA (7%), Nature (6.5%), Science (4.6%), Lancet (3.9%), and the New England Journal of Medicine (2.6%; Lewison & Turnbull, 2010). Clinical articles were more commonly cited than other article types (Lewison, Tootell, Roe, & Sullivan, 2008).…”
Section: Academic-related News Coveragementioning
confidence: 99%
See 1 more Smart Citation
“…A third were about breast cancer followed by lung (10%), prostate (8%), and skin (6%) cancer. Journalists working for the New Scientist read and use a wide range of academic journals, especially general and medical titles including Proceedings of the National Academy of Sciences of the USA (7%), Nature (6.5%), Science (4.6%), Lancet (3.9%), and the New England Journal of Medicine (2.6%; Lewison & Turnbull, 2010). Clinical articles were more commonly cited than other article types (Lewison, Tootell, Roe, & Sullivan, 2008).…”
Section: Academic-related News Coveragementioning
confidence: 99%
“…Some science magazines have the translation of scientific research for a nonspecialist public as their main goal. Journalists working for the New Scientist read and use a wide range of academic journals, especially general and medical titles including Proceedings of the National Academy of Sciences of the USA (7%), Nature (6.5%), Science (4.6%), Lancet (3.9%), and the New England Journal of Medicine (2.6%; Lewison & Turnbull, ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the above focused investigations into the types of research reported in the press, there is no quick method to e stimate the number of citations to academic journals on a large scale from full-text newspaper articles. Previous studies have employed either content analysts or coders to investigate small random or complete samples of news stories from a narrow set of sources (e.g., Clark & Illman, 2006;Lewison & Turnbull, 2010;Mellor, Webster, & Bell, 2011;Weitkamp, 2003), or have read complete sets of news stories to identify mentions of collections of journal articles (e.g., Bartlett, Sterne, & Egger, 2002). Some previous studies have automatically identified relevant articles using keyword queries in news databases (e.g., Lexis-Nexis) to identify mentions of named medicines (Moynihan et al, 2000) but this method only works for topics with a finite set of keywords and a more general automatic method is needed.…”
Section: Research Papermentioning
confidence: 99%
“…Major UK newspaper stories about biomedical research in 2001 cited New Scientist (7% -a magazine rather than a journal), British Medical Journal (6%), Lancet (4%) and Nature (3%) (Lewison, 2002). In 2008-9, the UK-based weekly science magazine New Scientist drew mainly from Proceedings of the National Academy of Sciences of the USA (7%), Nature (6.5%), Science (4.6%), Lancet (3.9%), and New England Journal of Medicine (2.6%) (Lewison & Turnbull, 2010). News stories about cancer in major US newspapers in 2003 mostly cited New England Journal of Medicine, Journal of the National Cancer Institute, and Journal of the American Medical Association (Moriarty, Jensen, & Stryker, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The exceptions to this are popular science magazines: publications such as New Scientist and Scientific American that deliver scientific news via articles and features like a newspaper, but cite the sources of information like a journal [12]. Blogging can enable scientists to directly engage the public in ‘good science’, focusing on their own area of expertise with an authority and depth that cannot be achieved by most newspaper or magazine articles.…”
Section: Informal Communicationmentioning
confidence: 99%